DISADVANTAGES OF THE SYSTEM OF TAXATION OF SUBSOIL USE AND WAYS TO IMPROVE IT - S. Mamaev (Вестник университета, 2016)
The article discusses the main taxes payable by subsoil users today. This export customs duties on oil and gas and the tax on mineral extraction. The main drawback of the tax on extraction of minerals is a flat scale of its use that are subject to the same rate as highly profitable and low-profitable deposits. It custo causes deposits that could be still long enough to be operated, preserved. In this regard, we consider it necessary to differentiate the mineral extraction tax rate and to abandon the fiscal role of customs duties.